Cost-Effectiveness Analysis of Camrelizumab Versus Chemotherapy as Second-Line Treatment of Advanced or Metastatic Esophageal Squamous Cell Carcinoma - Cai, Hongfu; Xu, Baohua; Li, Na; Zheng, Bin; Zheng, Zhiwei; Liu, Maobai (Frontiers in Pharmacology, 2021)
BACKGROUND: This study aimed to analyze the cost effectiveness of camrelizumab in the second-line treatment of advanced or metastatic esophageal squamous cell carcinoma in China. METHODS: On the basis of the ESCORT clinical trial, a partitioned survival model was constructed to simulate the patient’s lifetime quality-adjusted life years (QALYs), lifetime costs, and incremental cost-effectiveness ratio (ICER). One-way sensitivity and probability sensitivity analyses were performed to test the stability of the model. RESULTS: Treatment of esophageal squamous cell carcinoma with camrelizumab added 0.36 QALYs and resulted in an incremental cost of 1439.64 compared with chemotherapy, which had an ICER of 3999 per QALY gained. The ICER was far lower than the threshold of willingness to pay for one time the GDP per capita in China. Sensitivity analysis revealed that the ICERs were most sensitive to the cost of drugs, but the parameters did not have a major effect on the results of the model. CONCLUSIONS: Camrelizumab is likely to be a cost-effective option compared with chemotherapy for patients with advanced or metastatic esophageal squamous cell carcinoma. This informs patient selection and clinical path development.